Editorial for Special Issue “Envisioning the Future of Mining” - Juan M. Menéndez-Aguado; Oscar Jaime Restrepo Baena; Jessica M. Smith (Mining, 2023)
According to the International Energy Agency, clean energy transitions significantly increase strategic minerals demand [...]